Monitoring the agri-food system in Myanmar: Food vendors - July 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Most food retail prices in July 2021 were found to be higher than in the same period in 2020. Retail prices of the cheapest variety of rice–by far the most important staple in Myanmar–have risen by 13 percent, on average. Relative to a year ago, national-level food price inflation in July 2021 stood at 7 percent. Food price inflation was relatively higher in rural versus urban areas and in the Dry Zone and the Coastal areas. Households in the poorest quintile faced much higher food price inflation (10.4 percent) than those in the richest quintile (4.3 percent) as rice and cooking oils, which prices have increased substantially over the last year, are relatively more important in the poor’s food basket. Over the last year, prices rose most rapidly in the first half of 2021; the cost of a food basket in July 2021 was 8 percent higher than in December 2020. Food availability is seemingly not a challenge at the national level in July 2021. Food vendors report that the availability of most commodities is comparable to the same period in a normal year. About three-quarters of food vendors indicate that customers are buying less animal-sourced foods (i.e., chicken and pork) compared to normal periods. This likely is an indication of reduced consumer income as well as higher prices for those products. COVID-19 prevention measures were widely practiced by market vendors in 2020. However, they had been abandoned by a substantial share of the vendors surveyed in May 2021. Adoption rates in July 2021 improved compared to the previous survey round in May 2021 but were still below 2020 levels.